The wolfpack [videorecording (DVD)] - Moselle, Crystal; Angulo, Bhagavan; Angulo, Govinda; Angulo, Jagadisa; Angulo, Krsna; Angulo, Mukunda; Angulo, Narayana (Magnolia Home Entertainment, 2015)
The six Angulo brothers have grown up in their Manhattan apartment, home schooled by their parents, rarely if ever leaving their apartment. Their only connection to the outside world is television and the movies they watch and act out, complete with homemade costumes, in the apartment. When one of the brothers sneaks out for a few days on his own, the whole family dynamic is changed when he returns home.